Spor Bilimleri Fakültesi Öğrencilerinin Empatik Eğilim ve Yanal Düşünme Eğilimi Becerilerinin İncelenmesi - Arslan, Hayati; Ünver, Şaban; Yılmaz, Metin (Hasan ŞAHAN, 2022)
Bu araştırmanın amacı spor bilimleri fakültesi öğrencilerinin empatik eğilim ve yanal düşünme eğilimi becerilerini incelemektir. Araştırmanın evrenini 2020-2021 eğitim öğretim yılı güz döneminde Ondokuz Mayıs Üniversitesi Spor Bilimleri Fakültesi’nde öğrenim görmekte olan öğrenciler, örneklem grubunu ise tesadüfi örnekleme yöntemi ile belirlenmiş ve araştırmaya gönüllü olarak katılan 489 öğrenci oluşturmaktadır. Araştırma verilerini toplamak amacıyla Dökmen (1988) tarafından geliştirilen ve 20 maddeden oluşan Empatik Eğilim Ölçeğinin yanı sıra Semerci (2016) tarafından geliştirilen ve 9 maddeden oluşan Yanal Düşünme Eğilimi Ölçeği kullanılmıştır. Verilerin analizinde SPSS 22 paket programı kullanılmıştır. Bağımlı değişkenler arasındaki ilişki durumunu saptamak amacıyla “Pearson Korelasyon Analizi” gerçekleştirilmiştir. Sonuç olarak araştırmaya katılan spor bilimleri fakültesi öğrencilerinin empatik eğilim düzeylerinin ve yanal düşünme becerilerinin iyi seviyede olduğu görülmüştür. Kadın öğrencilerin erkek öğrencilere göre empatik eğilim becerilerinin daha gelişmiş olduğu belirlenmiştir. Ayrıca ölçekler arasındaki ilişkinin pozitif yönlü ve anlamlı olduğu saptanmıştır.

The aim of this research is to examine the empathic tendency and lateral thinking tendency skills of the students of the faculty of sports sciences. The population of the research consisted of students studying at the Faculty of Sports Sciences of Ondokuz Mayıs University in the fall semester of the 2020-2021 academic year, and the sample group was composed of 489 students who were determined by random sampling method and participated in the study voluntarily. In order to collect the research data, both the Empathic Tendency Scale developed by Dökmen (1988) and consisted of 20 items, and the Lateral Thinking Tendency Scale consisted of 9 items developed by Semerci (2016) were used. SPSS 22 package program was used in the analysis of the data. “Pearson Correlation Analysis” was performed to determine the relationship between dependent variables. As a result, it was seen that the empathic tendency levels and lateral thinking skills of the sports science faculty students participating in the research were at a good level. It was determined that female students' empathic tendency skills were more developed than male students. In addition, the relationship between the scales was found to be positive and significant.
Investigation of Empathic Tendency and Lateral Thinking Tendency Skills of Faculty of Sport Sciences Students
Keywords: Sports Science and Exercise; Egzersiz ve Spor Bilimleri